Students Attendance System (SAS) - Ramli, Aimran; Abdul Latip, Mohd Hanapi; Mohamed, Hasiah; Mohd Adzmi, Nurul Husna Amalina (International Journal of Advanced Science Computing and Engineering, 2019)
In UiTM Terengganu, student attendance current manual process is based on Academic Affairs (HEA) criteria. Lecturer has to bring attendance sheet to each class and take student attendance. At the end of semester lecturer has to manually calculate and send the report to HEA. Based on preliminary study, current process causing inefficiency on processing reporting. In order to improve the current process, Student Attendance System (SAS) is a system proposed to be developed for Universiti Teknologi MARA (UiTM) Terengganu. Lecturer is the primary users of the system. These allow user control, update, and view the attendance based on session, course and group. SAS was developed with System Development Life Cycle based on Extreme Programming (XP). XP phases involve phase of select user stories for release, then break down stories to tasks, plan release, develop, release to evaluate it. Then, process is repeated until meet user requirement. System testing based on test plan has been conducted. As for the evaluation, the evaluation process is done by three (3) experts then comment and suggestion is produced. Results based on experts evaluation shows that positive feedback from the experts where the development of SAS caters elements of ease of use, flow is easy to be understood and the system is consistent and follow the standard As conclusion, SAS can be improved based on comments and suggestions form experts and it has a big potential to be implemented in UiTM Terengganu.